Perkebunan Karet dan Kebangkitan Ekonomi di Afdeeling Indragiri Tahun 1920-An - Dedi Arman (Badan Riset dan Inovasi Nasional (BRIN), 2023)
Riau Province is currently one of the largest rubber producing regions in Indonesia. Rubber was produced by two regencies, namely Indragiri Hulu and Kuantan Singingi, which during the Dutch colonial era were included in the Indragiri Afdeeling area, Riau Residency. The existence of rubber plantations in Riau can be traced to its historical roots. This paper aims to examine the history of rubber plantations in the Indragiri Afdeeling in the 1920s. Writing using historical research methods. From the study it can be concluded that rubber has been planted in the Indragiri Afdeeling since 1910 but grew rapidly in the 1920s. Rubber is exported directly to Singapore. The existence of rubber plantation has an impact on the regional socio-economic revival. Among them, the people of Indragiri became heterogeneous due to the large number of migrants working in rubber plantations. A few highways, houses, and markets were built. Sea and land transportation is more available. More and more residents of Indragiri are going on the pilgrimage and also sending their children outside the residential area to study. The economic revival caused by rubber plantations in Indragiri ended after the world economic depression known as the malaise began in 1929. The world price of rubber fell, and farmers were reluctant to plant rubber anymore. Keywords: history, rubber plantations, economic revival, Indragiri